MODERN ARCHITECTURAL PRINCIPLES IN THE PRUITT-IGOE FAILURE AS THE END OF THE MODERN ARCHITECTURAL ERA (Journal of Architectural Research and Education, 2024)
Over a hundred years ago, modern architecture was developed in response to the fundamental changes in society's view of the world brought about by the industrial revolution. The aim was to find solutions to the new problems created by these changes. Pruitt-igoe was built in the post-war world, when there was a housing shortage, and was completed in 1956. The project was initially thought to be a sign of the success of modern architecture. Initially, Pruitt-Igoe was designed to contain a variety of housing types for different population levels. However, due to changes in the cost budget, the design had to be altered to maximize units by eliminating and lowering the quality of the original plan. The architect on the Pruitt-igoe project, Yamasaki tried to apply Le Cobusier's design method by creating green spaces and public spaces within. However, this was hindered by the responsible agency for intervening so that in the end Yamasaki removed or minimized many of the main features of the Pruitt-Igoe project. Pruitt-Igoe as a reflection of modern architecture is certainly very close to the doctrines of modern architecture. Modern architecture generally focuses on function, efficiency, and the use of modern materials and technology. However, the implementation of this design faced several problems, such as a lack of attention to the social and psychological factors of its inhabitants. The failure of Pruitt-Igoe shows that the application of modern architectural doctrines is not enough, and it also gave birth to a new era in architecture, the postmodern era. Thus, Pruitt-Igoe provides an important lesson that modern architecture needs to pay attention to social and psychological aspects in its design.